Zeolite addition to improve biohydrogen production from dark fermentation of C5/C6-sugars and Sargassum sp. biomass - R. M. Silva (Nature Portfolio, 2021)
Abstract Thermophilic biohydrogen production by dark fermentation from a mixture (1:1) of C5 (arabinose) and C6 (glucose) sugars, present in lignocellulosic hydrolysates, and from Sargassum sp. biomass, is studied in this work in batch assays and also in a continuous reactor experiment. Pursuing the interest of studying interactions between inorganic materials (adsorbents, conductive and others) and anaerobic bacteria, the biological processes were amended with variable amounts of a zeolite type-13X in the range of zeolite/inoculum (in VS) ratios (Z/I) of 0.065–0.26 g g−1. In the batch assays, the presence of the zeolite was beneficial to increase the hydrogen titer by 15–21% with C5 and C6-sugars as compared to the control, and an increase of 27% was observed in the batch fermentation of Sargassum sp. Hydrogen yields also increased by 10–26% with sugars in the presence of the zeolite. The rate of hydrogen production increased linearly with the Z/I ratios in the experiments with C5 and C6-sugars. In the batch assay with Sargassum sp., there was an optimum value of Z/I of 0.13 g g−1 where the H2 production rate observed was the highest, although all values were in a narrow range between 3.21 and 4.19 mmol L−1 day−1. The positive effect of the zeolite was also observed in a continuous high-rate reactor fed with C5 and C6-sugars. The increase of the organic loading rate (OLR) from 8.8 to 17.6 kg m−3 day−1 of COD led to lower hydrogen production rates but, upon zeolite addition (0.26 g g−1 VS inoculum), the hydrogen production increased significantly from 143 to 413 mL L−1 day−1. Interestingly, the presence of zeolite in the continuous operation had a remarkable impact in the microbial community and in the profile of fermentation products. The effect of zeolite could be related to several properties, including the porous structure and the associated surface area available for bacterial adhesion, potential release of trace elements, ion-exchanger capacity or ability to adsorb different compounds (i.e. protons). The observations opens novel perspectives and will stimulate further research not only in biohydrogen production, but broadly in the field of interactions between bacteria and inorganic materials.